EMPLOYEE MOTIVATION & PERFORMANCE: A COMPARATIVE STUDY BETWEEN THE EMPLOYEES OF PHED, BIHAR & DWSS, PUNJAB - Gautam, Manish Kumar; Chhura, Bikashdev; Kumar, ⁠Sanjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the intricacies of employee motivation and performance within two distinct government departments: The study was conducted among selected villages in Bihar with the participants coming from the Public Health Engineering Department (PHED) in Bihar and the Department of Water Supply and Sanitation (DWSS) in Punjab. The research’s objective is to examine the extent to which various environmental, organisational, and socio-demographic variables impact organisational motivation and employee performance within these departments. People motivation is one of the key factors of organizational performance, having a close and direct effect on production, satisfaction, and effectiveness. The research work uses a comparative technique to assess motivational factors and performance measures in two organisations, PHED and DWSS. Using paper and online questionnaires, interviews and secondary data analysis, the research establishes and compares the motivational forces as job security, recognition, company’s career development prospects, work-life balance and job performance in the departments of the company. The results imply that there are critical distinctions in motivational factors in the two departments owing to region based socio-economic forces, organizational culture and management practices. For instance, whereas, employees in the PHED Bihar might be much concerned about job tenure and security because of development picture of the region, on the other hand, DWSS Punjab employees might be more concern with career mobility and status because of the progressive organizational culture of the state. Additional findings include the relationship between leadership behaviours, management of employee engagement, and availability of resources on performance measures. The comparative analysis provides useful information on how and why such motivational theory can increase employee performance across the organizations. This work advances the knowledge concerning the key factors that influence the motivational and performance outcomes of public sector employees, as well as offering suggestions for practical organisational reform to boost productivity and morale.